2000
DOI: 10.1093/ejo/22.5.519
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rapid maxillary expansion on skeletal, dental, and nasal structures: a postero-anterior cephalometric study

Abstract: The purpose of this study was to compare the transverse dimensions of skeletal, dental, and nasal structures of a group of patients with maxillary narrowness before and after rapid maxillary expansion (RME) with an untreated control group using postero-anterior (PA) cephalometric radiographs. The material consisted of PA cephalograms of 25 children with a posterior crossbite (mean age 13 years 4 months), and 25 age- and sex-matched controls (mean age 13 years 11 months). Both groups consisted of 20 females and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
96
0
14

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(116 citation statements)
references
References 31 publications
6
96
0
14
Order By: Relevance
“…The expansion is often pyramidal in shape with the greatest expansion around the region of the nasal aperture. [4][5][6][7][8] Studies based on twodimensional lateral cephalograms have shown that the maxilla displaces downwards and forwards to a varying degree following RME treatment. 9 One of the most noticeable dental effects during RME activation is a diastema between the upper central incisors but tipping of the maxillary posterior teeth and alveolar processes laterally have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The expansion is often pyramidal in shape with the greatest expansion around the region of the nasal aperture. [4][5][6][7][8] Studies based on twodimensional lateral cephalograms have shown that the maxilla displaces downwards and forwards to a varying degree following RME treatment. 9 One of the most noticeable dental effects during RME activation is a diastema between the upper central incisors but tipping of the maxillary posterior teeth and alveolar processes laterally have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…These are technical problems such as loosening or breakage of the expander and biological problems such as pain, 2 nonopening of the midpalatal suture, 3 dental tipping, 4 root resorption of the anchor teeth, 5 gingival recession, 6 widening of the nasal root and nasal bridge, 7 swelling and reddening, 8 and occurrence of nasal septum asymmetries. 8 Root resorption occurs because of individual biologic and genetic predisposition and the effect of mechanical factors.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Traditionally, the effects of RME are evaluated using casts and/or two-dimensional (2D) radiographs, but reproducibility of 2D radiographs is problematic, and overlapping images are difficult to assess. [16][17][18] Conebeam computed tomography (CBCT) provides more accurate and reproducible imaging 19,20 for assessing all craniofacial skeletal structures, including the circummaxillary sutures. [21][22][23] Common RME appliances are the bonded (McNamara type) [24][25][26][27] and the tooth banded (Hyrax type).…”
Section: Introductionmentioning
confidence: 99%